KINERJA USAHA AGROINDUSTRI KELANTING DI DESA KARANG ANYAR KECAMATAN GEDONGTATAAN KABUPATEN PESAWARAN - Sagala, Imelda Castarica; Affandi, Muhammad Irfan; Ibnu, Muhammad (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This study aims to analyze the performance and value added of kelanting agroindustry. Kelanting is kind of snack made from cassava. Karang Anyar Village Gedongtataan District of Pesawaran Regency was chosen as a research site. The respondents consisted of 25 actors in agroindustry of kelanting. Data collection was conducted from July to August 2012. Methods of data analysis for (1) performance are reported net loss/profit, productivity, and capacity, and (2) value added is Hayami method. The results showed that: (1) Performance of kelanting agroindustry was good based on the R/C ratio of 1.24 (R/C > 1), the productivity was 16.07 kg per HOK (>7.2 kg/HOK), and the capacity was 0.92 (>0.5). (2) Value added of kelanting was Rp1,184.02 per kilogram of cassava or 34.57 percent.